EVALUASI PROGRAM KELUARGA HARAPAN (PKH) UNTUK KESEJAHTERAAN MASYARAKAT KOTA BATU - Eduardus Edu; Abd. Rohman (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Poverty is a problem faced by all countries in the world, including Indonesia. Therefore everycountry competes to strive for the welfare of its people. The Family Hope Program is a program that aimsto break the chain of poverty, but in its journey there are many obstacles and problems which includedata on recipients, distribution of aid, misappropriation of assistants and so on. This study aims todetermine the evaluation of PKH and its inhibiting factors and supporters in the Social Service Office ofBatu City. This study uses a qualitative descriptive approach with the technique of determininginformants using snowball sampling, and data analysis is done by data reduction, data presentationandconclusion. The results of the study indicate that this program is able to break the chain of poverty byhelping recipients meet their daily needs. In addition, PKH is able to encourage recipients to comply withthe terms and obligations provided as the main means of the education process. However, there are stillother things that are used as material for evaluating the implementation of PKH, namely the accuracy ofthe targets of some PKH recipients whose data received from the center or BPS sometimes does notmatch the conditions in the field.Keywords: Policy Evaluation, PKH, WelfareAbstrak: Kemiskinan merupakan masalah yang dihadapi oleh semua negara di dunia, termasukIndonesia. Oleh karena itu setiap negara berlomba-lombaberupaya untuk mensejahterakan rakyatnya.Program Keluarga Harapansebagai program yang bertujuan memutuskan mata rantai kemiskinan, namundalam perjalannya banyak sekali kendala dan masalah yang antara lain mencakup data penerima,penyaluran bantuan, penyelewengan pendamping dan sebagainya.Penelitian ini bertujuan untukmengetahui evaluasi PKH serta faktor penghambat dan pendukungnyadi Dinas Sosial Kota Batu.Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik penentuan informanmenggunakan snowball sampling, serta analisis datadilakukan denganreduksi data, penyajian datadanpenarikan kesimpulan.Hasil penelitian menunjukkan bahwa program ini mampu untuk memutus matarantai kemiskinan dengan membantu penerima memenuhi kebutuhannya sehari-hari. Selain itu PKHmampu mendorong penerima mematuhi syarat dan kewajiban yang diberikan sebagai sarana utama prosesedukasi. Namun demikian, masih ada hal lain yang menjadi bahan evaluasi pelaksanaan PKH yaituketepatan sasaran sebagian penerima PKH yang mana data yang diterima dari pusat atau BPS terkadangtidak sesuai dengan keadaan dilapangan.Kata Kunci: Evaluasi Kebijakan, PKH, Kesejahteraan